Le paysagiste est-il un expert ? - Pierre Donadieu (Projets de Paysage)
As in most of the professions, it exists beyond the landscapers, a field and a competence of expertise, an excellence in knowledge and savoir-faire to which the public and private institutions resort. What does this expertise exactly refer to ? How can we identify it ? Why do we need this expertise ? We will discuss the distinction between the three categories of expertise, which have in common the emphasizing of the values giving sense to landscapes and perceived spaces. The scientific and technical expertise differs from the expertise of the man of art (the designer) and of the criticism. However, in practice there are inseparable, even though they can weaken one to the others ; the challenge of expertise refers to the values granted to landscapes. Nevertheless, they can be distinguished from the expertise of the inhabitant, in particular in the perception of landscape defined as heritage (natural and cultural).